Boylston Street, ca. 1860-80 - Unknown (Tufts Archival Research Center, 2005)
Street level view looking northeast toward Berkeley Street from the intersection of Boylston and Clarendon Streets. On the right side of the photograph is the Rogers building on the campus of the Massachusetts Institute of Technology and to the right of that a partial view of the Museum of Natural History. A street light is in the foreground. 6 1/2 x 9 1/4 overall 10 1/2 x 13 3/8 Photographs